Personality and environmental behavior: perspectives of employees working in green and non-green restaurants - Alcorn, Michelle Ranae (Kansas State University, 2018)
As restaurants continue to be a major contributor to the economy, operations continue to negatively impact the environment. Within the industry, sustainability initiatives are becoming more popular, however, success depends on the buy-in of employees. The purpose of this study was to examine the relationship between and impact of personality traits on environmentalism of restaurant employees. By detecting personality traits associated with environmentalism, a better understanding of environmental behavior is obtained. This understanding can be used to motivate pro-environmental behaviors of employees by tailoring sustainability programs to appeal to different personalities. Employees working in green certified and non-certified restaurants completed a 95-item questionnaire measuring environmental attitude, personal conservation behavior, on-the-job environmental behavior, personality, and demographics. Data collection was completed using three methods: on-site, mailed questionnaires, and online. A total of 229 questionnaires were completed. A significant relationship existed between personality and environmentalism. Specifically, personality was a significant predictor of environmental attitude, personal conservation behavior, and on-the-job environmental behavior. Employees working in green certified restaurant operations had significantly higher levels of agreeableness, conscientiousness, extraversion, openness, environmental attitude, personal conservation behavior, and on-the-job environmental behavior and lower levels of neuroticism than employees working in non-certified restaurant operations. Findings from this study contribute to understanding the factors that impact environmental behavior. Potential environmental champions can be identified by their personality traits and encourage other employees to perform green practices. Furthermore, recruitment of employees exhibiting these pro-environmental traits could increase environmental performance in restaurant operations. Additionally, training and educational programs could be formatted based on the differences among personality traits to elicit pro-environmental behaviors of employees.
Keywords: restaurant employee; environmental sustainability; green restaurant; environmentalism; personality